Association of epicardial fat thickness with clinical and polysomnographic parameters in non-obese obstructive sleep apnoea patients. Issue 5 (23rd April 2018) - Derin, S; Altun, I; Koseoglu, S; Sahin, C; Yilmaz, M; Akin, F; Sahan, M
Abstract: Objectives: This study aimed to investigate the relationship of epicardial fat thickness with severity of obstructive sleep apnoea, and clinical and polysomnographic parameters, and to determine independent predictors for epicardial fat thickness. Methods: A total of 84 patients with a body mass index of less than 30 kg/m 2 and suspected sleep-disordered breathing were included in the study. The correlations of epicardial fat thickness with polysomnographic and clinical data, and severity of obstructive sleep apnoea, were investigated. Results: Mean epicardial fat thickness was 3.75 ± 1.07 mm in the study group ( n = 62) and 2.97 ± 0.62 mm in the control group ( n = 22) ( p < 0.001). There were significant positive correlations between epicardial fat thickness and: apnoea/hypopnoea index, oxygen desaturation index 3 and minimum oxygen saturation, as well as with age, body mass index, and neck and waist circumferences. Conclusion: Non-obese obstructive sleep apnoea patients have thicker epicardial fat compared to controls. Oxygen desaturation index 3 has a strong correlation with epicardial fat thickness and is an independent predictor of it.